INTERCULTURAL COMMUNICATION AND ITS SIGNIFICANCE FOR PROFESSIONAL ACTIVITIES OF FUTURE SPECIALISTS - Halytska, Mayya M. (Educological discourse, 2014)
This article analyzes the concept of «communication», «іntercultural сommunication», «speech etiquette». The problem of formation of ability of the individual to effective cross-cultural communication as a means of understanding the mental peculiarities of different cultures, which guarantees an effective dialogue between cultures in the world. Emphasized the important role of speech ethics in the intercultural communication. Submitted the characteristic of the cross-cultural misunderstandings in the communication process.